1982
DOI: 10.1002/art.1780250402
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predictors of patient response and side effects in the treatment of rheumatoid arthritis with a high dose nonsteroidal antiinflammatory drug regimen

Abstract: Clinical, laboratory, genetic, and radiologic studies were evaluated for 18 patients with rheumatoid arthritis who were treated for a mean of 16.6 months with a regimen involving supplementary aspirin and piroxicam, an investigational, nonsteroidal antiinflammatory agent. Although improvement in disease activity was seen, progression was evident on successive radiographs. Disease activity was not associated with the presence of any of the genetic markers. Peptic ulcers developed in 33% of patients, all of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Specific host characteristics that may determine susceptibility to H. pylori ‐associated diseases include gender, human leukocyte antigen genotypes, blood groups, gastric acid physiology and interleukin‐1 ( IL‐1 ) locus polymorphism [13,14]. Blood group O has traditionally been associated with the risk of developing duodenal ulcer (DU) [15,16]. Boren et al [17] recently demonstrated that the blood group Lewis b possessed receptors for H. pylori , and it was exposed only in individuals with blood group O.…”
mentioning
confidence: 99%
“…Specific host characteristics that may determine susceptibility to H. pylori ‐associated diseases include gender, human leukocyte antigen genotypes, blood groups, gastric acid physiology and interleukin‐1 ( IL‐1 ) locus polymorphism [13,14]. Blood group O has traditionally been associated with the risk of developing duodenal ulcer (DU) [15,16]. Boren et al [17] recently demonstrated that the blood group Lewis b possessed receptors for H. pylori , and it was exposed only in individuals with blood group O.…”
mentioning
confidence: 99%